Cognitive differences among first-year and senior engineering students when generating design solutions with and without additional dimensions of sustainability. (8th February 2021) - Hu, Mo; Shealy, Tripp; Milovanovic, Julie
Abstract: The research presented in this paper explores how engineering students cognitively manage concept generation and measures the effects of additional dimensions of sustainability on design cognition. Twelve first-year and eight senior engineering students generated solutions to 10 design problems. Half of the problems included additional dimensions of sustainability. The number of unique design solutions students developed and their neurocognitive activation were measured. Without additional requirements for sustainability, first-year students generated significantly more solutions than senior engineering students. First-year students recruited higher cortical activation in the brain region generally associated with cognitive flexibility, and divergent and convergent thinking. Senior engineering students recruited higher activation in the brain region generally associated with uncertainty processing and self-reflection. When additional dimensions of sustainability were present, first-year students produced fewer solutions. Senior engineering students generated a similar number of solutions. Senior engineering students required less cortical activation to generate a similar number of solutions. The varying patterns of cortical activation and different number of solutions between first-year and senior engineering students begin to highlight cognitive differences in how students manage and retrieve information in their brain during design. Students' ability to manage complex requirements like sustainability may improve with education.